THE ROLE OF PRINCIPAL LEADERSHIP IN IMPROVING LEARNING EFFECTIVENESS IN KINDERGARTEN IN TANJUNG MORAWA DISTRICT - Sintya Kinanti Putri; Aman Simare-Mare (RADJA PUBLIKA, 2026)
This study aims to describe the role of principal leadership in improving learning effectiveness in Kindergarten at Tanjung Morawa District, including learning planning, academic supervision and coaching, creating a conducive learning climate, and learning effectiveness. This research used a quantitative descriptive approach with a sample of 30 kindergarten teachers selected through saturated sampling. The instrument used was a Likert scale questionnaire and data were analyzed using descriptive statistics. The results showed that all indicators were in the very good category: learning planning (3.62), academic supervision and coaching (3.52), creating a conducive learning climate (3.50), and learning effectiveness (3.70). Overall, the role of principal leadership obtained an average score of 3.53 in the very good category. The Pearson correlation test showed a value of 0.519, indicating a moderate positive relationship between principal leadership and learning effectiveness. The research hypothesis was accepted.